Marketing Strategies, Islamic Teachings, And Insurance Needs On Interest In Becoming Islamic Insurance Customers At Bank Muamalat Cirebon - Yadi Hendrawan; Shobihah Maemun Zubair; Ahmad Zaeni Dahlan; Ulfain; Muhammad Arwani (Journal of Islamic Economic Development, 2024)
This research is based on the idea that interest in becoming an Islamic insurance customer is influenced by marketing strategies, Islamic religious teachings, and the need for insurance. These variables are analyzed using the Ordinary Least Squares (OLS) method, with interest as the dependent variable and the other three variables as independent variables. The results showed that marketing strategies, Islamic religious teachings, and insurance needs partially had a positive and significant effect on interest in becoming Islamic insurance customers at Bank Syariah Cirebon City, with insurance needs as the most dominant variable. The implications of these findings suggest that Islamic financial institutions need to further customize marketing strategies and religious education approaches to increase the attractiveness of Islamic insurance for the community.